Embodied Transformation of Islamic Javanese Wayang Characters: Practice-Led Reconstruction of Limbuk–Cangik in Contemporary Muslim Cultural Performance - Ndaru Ranuhandoko; Bambang Sunarto; Winny Gunarti Widya Wardani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Grounded in a constructivist paradigm and informed by phenomenological and performativity-based perspectives, this study examines the embodied transformation of the Limbuk–Cangik characters in wayang kulit purwa as a form of cultural practice within Javanese Islam. The research conceptualizes artistic transformation as an epistemic process, in which the body functions as a site for the articulation and negotiation of Islamic ethical values. Accordingly, the paper aims to analyze how such transformations reconfigure the moral, social, and pedagogical functions of these characters in contemporary Muslim contexts. Methodologically, the study adopts a practice-led research design integrated with ethnographic fieldwork, including participatory observation, in-depth interviews with puppeteers, digital archive analysis, and visual studies. Data are analyzed using an interactive model of condensation, display, and verification, supported by triangulation across sources and methods. This approach enables the integration of experiential knowledge derived from artistic practice with empirical cultural analysis. The theoretical framework draws on cultural hermeneutics, embodiment theory, and theories of Islamic performativity, situating wayang as a medium through which religious values are materially and socially mediated. The findings indicate a shift from a ritualized shadow medium to a more communicative three-dimensional embodiment, which enhances audience engagement without diminishing ethical integrity. Rather than eroding Islamic moral values, this transformation reconstructs their social function through adaptive visual and performative strategies. This study contributes to the development of a practice-based framework in Islamic art studies by proposing the concept of visual cultural ijtihād, in which artistic practice operates as a mode of knowledge production. It further demonstrates that the reconstruction of tradition enables the expansion of cultural da’wah while sustaining its moral and cultural legitimacy in contemporary Muslim society.